Beispiel Nr: 01
$\text{Gegeben:}\\ \text{Bruch1: }a\dfrac{b}{c} \\ \text{Bruch2: }d\dfrac{e}{f} \\ \\ \text{Gesucht:} \\\text{Summe,Differenz,Produkt,Quotient} \\ a\frac{b}{c}- d\frac{e}{f}\\ \textbf{Gegeben:} \\ a=4 \qquad b=5 \qquad c=6 \qquad d=7 \qquad e=8 \qquad f=9\\ \\ \textbf{Rechnung:} \\\text{Hauptnenner: kgV( }6,9 \text{) }= 18 \\ \text{Erweiterungsfaktoren: }\frac{18}{6}=3 \qquad \frac{18}{9}=2 \\ \\\text{Summe}\\4\frac{5}{6}+7\frac{8}{9}=4+7+\frac{5\cdot3}{6\cdot3}+\frac{8\cdot2}{9\cdot2}= 11+\frac{15+16}{18}=11+\frac{31}{18}=12\frac{13}{18} \\ \\\text{Differenz}\\4\frac{5}{6}-7\frac{8}{9}=4-7+\frac{5\cdot3}{6\cdot3}-\frac{8\cdot2}{9\cdot2}= -3+\frac{15-16}{18}=-3+\frac{-1}{18}=-3\frac{1}{18} \\ \\\text{Produkt} \\ 4\frac{5}{6}\cdot 7\frac{8}{9}=\frac{4\cdot 6 +5}{6}\cdot \frac{7\cdot 9+ 8}{9}=\frac{29}{6}\cdot \frac{71}{9}=\frac{29\cdot71}{6\cdot9}= \frac{2,06\cdot 10^{3}}{54}=38\frac{7}{54} \\ \\\text{Quotient} \\ 4\frac{5}{6}:7\frac{8}{9}=\frac{4\cdot 6 +5}{6} :\frac{7\cdot 9+ 8}{9}=\frac{29}{6} :\frac{71}{9}= \frac{29}{6} \cdot \frac{9}{71}= \frac{261}{426}=0,613 \\ $